A Modified Diagonal Mesh Shuffle Exchange Interconnection Network - Akash Punhani; Pardeep Kumar; Nitin Nitin (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Interconnection network is an important part of the digital system. The interconnection mainly describes the topology of the network along with the routing algorithm and flow control mechanism. The topology of the network plays an important role on the performance of the system. Mesh interconnection network was the simplest topology, but has the limited bisection bandwidth on the other hand torus and diagonal mesh was having long links. The Modified diagonal mesh network tried to replace the torodial links but was having more average path length so in proposed topology we have tried to improve the average distance using shuffle exchange network over the boundary node. In this paper, we propose the architecture of Modified Diagonal Mesh Shuffle Exchange Interconnection Network. This Modified Diagonal Mesh Shuffle Exchange Interconnection network have been compared with four popular topologies that are simple 2D Mesh, 2D Torus, Diagonal Mesh and Modified Diagonal Mesh Interconnection Network on the four traffic patterns such as Bit Complement traffic, Neighbor traffic, Tornado traffic and Uniform traffic are used for comparisonand performance analysis. We have performed the analysis with a 5% and 10% of hotspot on the Uniform Traffic. The simulation results shows that the proposed topology is performed better on bit complement traffic and can also handle the other traffic up to certain level.